Technology Literation of PAUD Educators Bengkulu City - Yunita Puspitasari (Indonesian Journal of E-learning and Multimedia (IJOEM), 2023)
The research aims to identify the technology literacy of PAUD teachers in Bengkulu City. The data analysis technique in this study used a quantitative descriptive analysis technique. The data collection technique used in this study was a needs questionnaire which was distributed directly to PAUD teachers. This research was conducted in Bengkulu City in April. The population of this study were PAUD teachers from several PAUD, namely PAUD Delima, PAUD Al-khanza, PAUD Lukman Nur Hakim and PAUD Abdan Sakura. In this study, direct observation techniques and questionnaires were used by teachers to determine the level of needs and abilities of PAUD teachers for learning media that utilize educational technology. Data analysis techniques in this study used quantitative data analysis techniques and concluded quantitatively. Quantitative analysis techniques, in this case a questionnaire on the needs and abilities of PAUD teachers, are based on the answers to a research questionnaire filled out by 18 PAUD teachers. Each question item used in the questionnaire was tested for validity and reliability to find out whether the instrument was feasible to use to obtain the data needed by the researcher. In this study, the results of a needs questionnaire were obtained by 89%, meaning that teachers needed digital-based learning media, namely the use of technology. The results of distributing the teacher's ability questionnaire by obtaining results of 86% were in the very agree category. Based on the results of data analysis, it can be concluded that teachers already have the ability to use technology, but still need various direct applications.